Characterization of External Mucosal Microbiomes of Nile Tilapia and Grey Mullet Co-cultured in Semi-Intensive Pond Systems - Elsheshtawy, Ahmed; Clokie, Benjamin Gregory James; Albalat, Amaya; Beveridge, Allan; Hamza, Ahmad; Ibrahim, Abdelaziz; MacKenzie, Simon (Frontiers in Microbiology, 2021)
The external mucosal surfaces of the fish harbour complex microbial communities, which may play a pivotal role in the physiological, metabolic, and immunological status of the host. Currently, little is known about the composition and role of these communities, to which extent they are species and/or tissue specific and whether they reflect their surrounding environment. Co-cultured fish, a common practise in semi-intensive aquaculture, where different fish species cohabit in the same contained environment are an easily accessible and informative model toward understanding such interactions. This study provides the first in-depth characterisation of gill and skin microbiomes in co-cultured Nile tilapia (Oreochromis niloticus) and grey mullet (Mugil capito) in semi-intensive pond systems in Egypt using 16S rRNA gene-based amplicon sequencing. Results showed that the microbiome composition of the external surfaces of both species and pond water was dominated by the following bacterial phyla Proteobacteria, Fusobacteriota, Firmicutes, Planctomycetota, Verrucomicrobiota, Bacteroidota and Actinobacteriota. However, water microbial communities had the highest abundance and richness and significantly diverged from the external microbiome of both species, thus the external autochthonous communities are not a passive reflection of their allochthonous communities. The autochthonous bacterial communities of skin were distinct from gill in both species, indicating that the external microbiome is likely organ specific. However, gill autochthonous communities were clearly species-specific, whereas skin communities showed higher commonalities between both species. Core microbiome analysis identified the presence of shared core taxa between both species and pond water in addition to organ-specific taxa within and between the core community of each species. These core taxa included beneficial genera such as Uncultured Pirellulaceae, Exiguobacterium and Cetobacterium and opportunistic potential pathogens such as Aeromonas, Plesiomonas and Vibrio. This study provides the first in-depth mapping of bacterial communities in this semi-intensive system that in turn provides a foundation for further studies toward enhancing health and welfare of these cultured fish and ensuring sustainability.